Desenvolvimento de uma metodologia para previsão de trincas em engrenagens bi-helicoidais nas bobinadeiras dos laminadores Sendzimir sujeitas a danos acumulados por fadiga de contato - Douglas Matias Araújo Alvarenga (2017)
Sendzimir rolling mills are widely used in Stainless Steel plants. It uses winders (one at each side) to reel the steel strip. The winders are powered by a electric motor coupled with a pair of double helical gears, that in turn, is connected to a mandrel where the strip are reeled to form a coil. In this work was developed a methodology for life prediction of double helical gears at Sendzimir mill winders submitted to contact fatigue cumulative damage. The proposal of methodology is based on the gear fatigue cumulative damage, wherein every relevant parameter are introduced on the life prediction model. The Miners linear damage rule is used to quantify the damage on the gear at each turn it carry out. The main objective of this work is to propose a methodology to be used as a control tool to allow the prediction of gear maintenance/replacement in case it presents pittings. The methodology was applied in a experimental case that lasted 40 consecutive days, totalizing almost 1,5 E+06 cycles at gear teeth. It was verified that the operating Regime of lubrication has great influnce over the final cumulative damage, and it is highly affected by the torque and the oil temperature. The increase of process speed from 458 m/min to 600 m/min has not made a signifficant influence on the fatigue life regarding the proposed methodology. It was observed there is some gear features that are modified after it begins to work, being proposed to apply the methodology adjusting these features. The methodology does not contemplate abnormal process loadings, as such resulting from gear mounting failures.